Pemikiran Harun Yahya Dalam Nilai Nilai Moral Al-Qur’an ( Studi Analisis Nilai Nilai Pendidikan Akhlaq) - Ali Mustofa (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Moral education is a sub / part of the subject of Religious Education, because the real religion is morality, so that the presence of the Prophet Muhammad to the face of the earth was in the step of completing the morals of men who at that time, girls were killed alive, against the truth of many who resist, as well as many other levels of munkar they do. Because religion is morals, it is not excessive to say that what is good according to morals is good also according to religion. Because so much the role of education of Morals in the formation keperibadian son of man then all Muslim philosophers agree that moral education is the soul of Islamic education, because the highest goal of Islamic education is to educate the soul and morals. The values of moral education in the book value of moral values of the Qur'an on Islamic education based on human life together with what He has created. The Qur'an tells people to be dignified, humble, trustworthy, kind, faithful, adult, and willing to listen to goodness. values of moral education contained in the book